The importance of nutrigenomics and nutrigenetics in chronic non-communicable diseases (Research, Society and Development, 2024)
Nutrigenomics is a multidisciplinary scientific field that studies the interactions between diet, nutrients, genes, and how these interactions influence health and relate to chronic non-communicable diseases. Nutrigenetics, in turn, is the study focused on analyzing individual genetic variations and how they lead to changes in a person's immune response, affecting the absorption and metabolism of nutrients. Therefore, the objective of this work is to report the importance of nutrigenomics and nutrigenetics in relation to chronic non-communicable diseases, bringing knowledge on this topic. This work is a literature review consulting the SCIELO, PERIÓDICO CAPES and GOOGLE ACADÊMICO databases over the last 10 years. Overweight and obesity are considered important risk factors for the development of chronic non-communicable diseases and are associated with increased intake of industrialized and ultra-processed foods, which can lead to significant changes in people's diet. Therefore, research also suggests that certain bioactive food ingredients have the potential to influence key cellular and molecular events that prevent cancer. Bioactive ingredients have the ability to prevent lipid oxidation and have antioxidant principles, which are claimed to play an extremely important role. Prevent cardiovascular diseases and cancer.